Feasibility and impact of a Swedish fuel cell-powered rescue boat. (15th August 2021) - Chiche, Ariel; Andruetto, Claudia; Lagergren, Carina; Lindbergh, Göran; Stenius, Ivan; Peretti, Luca
Abstract: With the increasing interest for zero-emission vehicles, electric boats represent a growing area. Weight is a limiting factor for battery-powered boats, therefore, the use of fuel cell/battery systems is investigated. The present study examines the power requirements, the energy-storage solutions and the sustainability assessment of a light and fast rescue boat operating in the Swedish lake Barken. A weight-optimized hybrid fuel cell/battery system is presented. The results show that if the hydrogen storage is wisely selected, the weight of the hybrid system is significantly less than that of a battery system and can compete with an internal combustion engine system. The sustainability assessment highlights and compares the impact in terms of cost and emissions of the different energy storage solutions. The quantification of the emissions for the different energy systems under several scenarios shows a clear advantage for the electric solutions. Highlights: Hybrid fuel cell/battery system is the lightest way to electrify a fast rescue boat. Pure battery systems are too heavy to ensure the payload of the rescue boat. The hybrid system emits less than a diesel engine system after few missions. Funding is needed to develop the use of fuel cell in maritime applications.